USING FAILURE MODES AND EFFECTS ANALYSIS AS A PROBLEM-SOLVING GUIDELINE WHEN IMPLEMENTING SPC IN A SOUTH AFRICAN CHEMICAL MANUFACTURING COMPANY - Appollis, Logan-Lee Miché; Van Dyk, Wynand A; Matope, Stephen (The South African Journal of Industrial Engineering, 2020)
Quality management has ceased to be an operational extra, and has become imperative to doing business in a saturated market environment with demanding clients. It is now a significant component of holistic operational management. The ultimate aim remains customer satisfaction, using the most effective techniques to ensure the most efficient and cost-effective process. Statistical process control (SPC) and statistical quality control have been widely used in quality management to enhance process performance by reducing process variation. However, SPC can only be effective if implemented with a structured problem-solving tool. The diagnostic ability of statistics, coupled with a failure modes and effect analysis (FMEA) as the problem-solving methodology during an out-of-control action plan, creates an environment conducive to improving processes and empowering employees. The failure modes and effect analysis was used to identify and eliminate sources of variation, which led to a reduction in process variation by 63 per cent and a decrease in defects by 160 961 per million opportunities.